Nanotechnology: Sketching the next big thing in Malaysian context - Karim, M.E.; Munir, A.B. (2015)
Realizing the limitless prospects of nanotechnology, many countries in the world, irrespective of size and economy, have been investing and allocating considerable amount of funding. Innovative initiatives are also taken at both public and private sphere. Over the years, Malaysia has successfully established its competence in electrical and electronic, and chemical sectors, where nanotechnology is very prospective. The government of Malaysia has realized the importance of the nanoscale technology immediately when other countries initiated their respective moves to exploit it. Already hundreds of products containing the word "nano" in the product name are available in Malaysia market, and many companies have been commercializing nano-enhanced products in Malaysian markets. This article attempts to portray the different initiatives taken by the Malaysian policymakers in relation to nanotechnology research and development. Even though the policymakers have taken a good number of initiatives, there are many scopes to take more steps as some of Malaysia's neighbors have taken some serious and pragmatic initiatives to take lead.